Training Need of Rural Women Participating in Income Generating Activities of SUS - Yesmin, S; Rahman, MZ; Miah, MAM; Akhter, S (Progressive Agriculture, 2014)
The purposes of the study were to determine the extent of training need of rural women participating in IGAs supported by SUS (Sabalamby Unnayan Samity) and to relate the training need with their selected characteristics. Data were collected from 105 respondents of ten villages of Sadar Upazila of Netrokona district through interview schedule in April 2007. Most of the respondents were in high need of training for their better performance and participation in IGAs of SUS. The relationships between their characteristics and training need were tested by computing the co-efficient of correlation. Education, farm size, participation in IGAs and credit received were found positively correlated with their training need whereas age of the respondents showed negative significant relationship with their extent of training need. DOI: http://dx.doi.org/10.3329/pa.v18i2.18384 Progress. Agric. 18(2): 271 - 278, 2007